Acute Myotonometric Changes in the Masseter and Upper Trapezius Muscles After Upper Body Quarter Stretching and Coordination Exercises or Chewing - Marša Magdič; Miloš Kalc; Matjaž Vogrin (Applied Sciences)
Pathologies in neck and masticatory muscles affect muscle tone and biomechanical and viscoelastic properties, necessitating precise assessment for treatment. This study evaluated the impact of two guided interventions—relaxing exercises targeting the neck and masticatory muscles (“Exercise”) and heavy chewing using six chewing gums (“Chewing”)—on the masseter and upper trapezius muscles. Twelve participants (aged 19–40 years) underwent myotonometric assessment pre- and post-intervention, measuring tone, stiffness, decrement, relaxation time, and creep. The results showed significant changes in the masseter muscle after exercise, with increased stiffness (14.46%, p < 0.001) and tone (7.03%, p < 0.001) but decreased creep (−9.71%, p < 0.001) and relaxation time (−11.36%, p < 0.001). Conversely, chewing decreased stiffness (−8.82%, p < 0.001) and tone (−5.53%, p < 0.001), while it increased creep (9.68%, p < 0.001) and relaxation time (9.98%, p < 0.001). In the trapezius muscles, tone decreased after both interventions (Exercise: −7.65%, p < 0.001; Chewing: −1.06%, p = 0.003), while relaxation increased (Exercise: 1.78%, p < 0.001; Chewing: 2.82%, p < 0.001). These findings reveal the distinct effects of exercise and chewing on muscle properties, emphasising the complexity of their therapeutic potential and the need for further investigation.